PENGARUH AMPER LAS PADA PENGELASAN BAJA LUNAK DENGAN PENGELASAN SMAW PADA POSISI PENGELASAN 4F - Muhammad Tegar Dwicak Sono Egar; Tuparjono Tuparjono; Muhammad Haritsah Amrullah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Shielded Metal Arc Welding is one of the most widely used welding in welding work because it is easier and cheaper than other electric arc welding. In welding, welding defects often occur, welding defects are triggered by the use of amperes, welding speed, and the movement of the welding arc. In this study, the use of various amperes will be carried out, intended to determine which amperage is more optimal so that it can eliminate welding defects that occur. Experiments were carried out with the same welding parameters using different amperes, namely five samples of 85 ampere welding, five samples of 95 amperage welding, 5 samples of 105 ampere welding. The phenomenon of arc movement, welding speed will be observed using a camera so that its effect on the welding results is known. This study did not get the results of the use of the most optimal welding current so that the purpose of this study was not achieved, where the purpose of this study was the use of the most optimal welding current at the 4F welding position so as to eliminate welding defects that occurred in the SMAW welding. In the results of this study, it was found that there were welding defects in each variation of amperage used, namely amperes 85, amperes 95, amperes 105.